Increasing Community Health Knowledge in Karangrejo Village, Wungu District, Madiun Regency through Socialization, Mentoring, Cultivation and Utilization of Sambiloto Medicinal Plants. - William, Muhammad Reno; Latifah Gina; Alfi Magfirli; Kusuma, Yenny; Hutomo Mandala Putra; Arum Suproborini (Universitas Sahid Surakarta, 2024)
Health is still an important topic in Karangrejo Village, Wungu District, Madiun Regency. Quoted from the local health center, the level of infectious diseases such as flu and skin diseases is still high. This activity aims to increase knowledge about the cultivation and benefits of the bitter medicinal plant (Andrographis paniculata) for health in Karangrejo Village. The methods used include land surveys, education about the health benefits of these plants, land cleaning, fertilization, as well as planting and cultivation training. The results of the activity showed an increase in public knowledge about the cultivation of the bitter medicinal plant and its benefits for health. In conclusion, the socialization, mentoring, cultivation and use of Sambiloto activities are useful for increasing knowledge about the cultivation and health benefits of the bitter medicinal plant in Karangrejo Village, Wungu District, Madiun Regency.